2022
DOI: 10.3390/biomedicines10020413
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Sphingomyelinase Sensitizing Liposomes in Imaging Intestinal Inflammation in Dextran Sulfate Sodium-Induced Murine Colitis

Abstract: Inflammatory bowel disease (IBD) is characterized by chronic inflammation in the gastrointestinal tract, resulting in severe symptoms. At the moment, the goal of medical treatments is to reduce inflammation. IBD is treated with systemic anti-inflammatory compounds, but they have serious side effects. The treatment that is most efficient and causes the fewest side effects would be the delivery of the drugs on the disease site. This study aimed to investigate the suitability of sphingomyelin (SM) containing lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…We wanted to assess the success of targeting the liposomes to the macrophages in the implant site. Earlier, it was shown that monocytes; macrophage subtypes M1, M2; and colon cancer cell line Caco-2 effectively take up SM-liposomes in vitro [ 50 ]. However, in bone fraction studies, we wanted to focus on BMDM cells extracted from bone marrow in the rats’ femurs and inducing these BMDMs to macrophage to check the uptake of liposomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We wanted to assess the success of targeting the liposomes to the macrophages in the implant site. Earlier, it was shown that monocytes; macrophage subtypes M1, M2; and colon cancer cell line Caco-2 effectively take up SM-liposomes in vitro [ 50 ]. However, in bone fraction studies, we wanted to focus on BMDM cells extracted from bone marrow in the rats’ femurs and inducing these BMDMs to macrophage to check the uptake of liposomes.…”
Section: Discussionmentioning
confidence: 99%
“…The cell nuclei counterstaining was done with a DAPI solution final concentration of 0.1 µg/mL. The procedure has been previously demonstrated successfully [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…[136] For example, LEE et al [137] used esterase-unstable ester bonds on lipid fractions to attach radiotracers and validated the tracer potential of enzyme-responsive liposomes in specific tumor environments (Figure 8b). Recently, Medina et al [138] successfully constructed a specific liposome targeting the inflammatory region of dextran sodium sulphate-induced colitis in mice by using sphingomyelinase, which is only present extracellularly during cellular stress such as inflammation.…”
Section: Internal Stimulus Responsementioning
confidence: 99%
“…Inflammatory bowel disease (IBD) is a chronic inflammatory disorder of the gastrointestinal (GI) tract that comprises two primary forms: Crohn’s disease (CD) and ulcerative colitis (UC) [ 1 , 2 , 3 , 4 ]. CD is manifested by a transmural and discontinuous ulceration of any portion of the GI tract, mainly affecting the terminal ileum and the perianal region [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%